2022
DOI: 10.1038/s41467-022-30615-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of type 1 immunity with tofacitinib is associated with marked improvement in longstanding sarcoidosis

Abstract: Sarcoidosis is an idiopathic inflammatory disorder that is commonly treated with glucocorticoids. An imprecise understanding of the immunologic changes underlying sarcoidosis has limited therapeutic progress. Here in this open-label trial (NCT03910543), 10 patients with cutaneous sarcoidosis are treated with tofacitinib, a Janus kinase inhibitor. The primary outcome is the change in the cutaneous sarcoidosis activity and morphology instrument (CSAMI) activity score after 6 months of treatment. Secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 59 publications
1
36
0
2
Order By: Relevance
“…However, the number of patients with extra-cutaneous disease were small and the end points were poorly described. Nevertheless, this was an important validation of the original case reports ( 305 ).…”
Section: Studies With a Focus On Extra-pulmonary And Multi-organ Sarc...supporting
confidence: 72%
See 1 more Smart Citation
“…However, the number of patients with extra-cutaneous disease were small and the end points were poorly described. Nevertheless, this was an important validation of the original case reports ( 305 ).…”
Section: Studies With a Focus On Extra-pulmonary And Multi-organ Sarc...supporting
confidence: 72%
“…Damsky et al ( 305 ) recently published an open-label study of ten patients with cutaneous sarcoidosis. The authors found that treatment led to significant improvement of skin lesions using the previously validated cutaneous sarcoidosis activity and morphology instrument (CSAMI) scoring system.…”
Section: Studies With a Focus On Extra-pulmonary And Multi-organ Sarc...mentioning
confidence: 99%
“…On the other hand, IFN-γ is a T-helper cell type 1 (Th1) cytokine, previously demonstrated to be an efficient inducer of LGCs from human monocytes [23, 53]. In vivo , IFN-γ is found in human tuberculosis and leprosy granulomas [7, 54] and in non-infectious granulomatous disease such as sarcoidosis [55, 56] and Blau syndrome [57]. All these conditions are associated with the presence of LGCs and T cells (either Th1 or Th17) within the granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many of the listed cytokines implicated in sarcoidosis pathogenesis, including IFN-g and IL-2, IL-23, IL-4, and IL-13, act via the JAK-signal transducer and activator of transcription (STAT) pathway. As a confirmation, JAK-STAT pathway activation has been reported in patients with sarcoidosis [ 39 ], and JAK inhibitors represent one of the new therapeutic options for long-standing sarcoidosis [ 40 ].…”
Section: Immunopathology Of Sarcoidosis and Covid-19 Shared Mechanismsmentioning
confidence: 99%